Are Children Truly Investments? A Maslowian and Islamic Perspective on The Sandwich Generation Phenomenon - Mafrukha, Wahyu Nisawati; Maharani, Aisyah Puan; Ulya, Helmy Zulfikar; Assegaf, Fatimah; Nur, Fatikhatun; Thalgi, Mohammad J. (An-Nida', 2026)
This study seeks to investigate the phenomenon of the “sandwich generation” within contemporary Indonesian society from both psychological and religious perspectives. The significance of this research stems from the increasing dual burden faced by individuals who support their parents while simultaneously maintaining their own well-being, a situation that impacts mental health and family dynamics. Employing a qualitative methodology, this study explores the lived experiences of three informants who  bear concurrent financial and emotional responsibilities. Abraham Maslow’s hierarchy of needs theory is utilised to elucidate how the inability to satisfy basic and psychological needs may impede self-actualisation and adversely affect  psychological well-being. Concurrently, the philosophical insights of Syed Muhammad Naquib al-Attas are applied to critically examine the concept of birr al-wālidayn. The findings indicate that the condition of the sandwich generation precipitates anxiety, emotional exhaustion, role conflict, and diminished self-esteem as a consequence of familial and occupational pressures. Furthermore, family relationships tend to become more instrumental, with children assuming the role of primary financial providers. The study also demonstrates that interpreting birr al-wālidayn solely as a material obligation risks overlooking the values of ikhlāṣ (sincerity) and raḥmah (compassion). This research contributes to the field by providing a contextualised understanding of filial devotion that emphasises balance, ethical awareness, and individual capacity.